"Uber is here to stay": Exploring the policy implications of the Uber-Local taxis turf war in Accra, Ghana. Issue 1 (March 2020) - Agyemang, Ernest
Highlights: Uber partner drivers in Accra are mostly the youth and the well-educated class. Uber services are mostly concentrated in the University of Ghana campus and the Central Business District of Accra. Uber users hail the service for its relative high professionalism, courtesy and security. Local taxi operators perceive Uber as illegal and unfair. Ghana's present regulatory framework seems unprepared for ride hailing services.